Pengembangan Kartu Permainan Untuk Meningkatkan Keterampilan Membaca Tahap Permulaan Siswa Kelas I SD/MI Dengan Teknik Tandur Quantum Teaching - Zainul Fuad (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
The general focus of this research is the development of flash card that using the TANDUR technique, while the particular focus is the process of developing game cards and the quality of game cards including validity, practicality and effectiveness. This type of development research uses a 4-D development model which includes: 1) define, 2) design, 3) develop, 4) disseminate. Research data are grouped into qualitative and quantitative data. Data collection techniques were carried out by observation, questionnaires, tests, and interviews. The results of the game card research developed were categorized as very valid with details of validity percentages (81.74%). In the realm of practicality categorized as very practical in terms of student responses by scores (100%), and teacher responses by scores (95%). The realm of effectiveness is categorized as very effective in terms of the analysis of student activities by scores (87.14%), observing teacher activities by scores (90%), and student learning outcomes can achieve completeness by scores (97%).